Chronic Kidney Disease and Cardiovascular Disease: Is there Any Relationship? - Vallianou, Natalia G.; Mitesh, Shah; Gkogkou, Agathoniki; Geladari, Eleni (Current Cardiology Reviews, 2019)
Introduction: Chronic Kidney Disease is a growing health burden world wide. Traditional and mutual risk factors between CVD and CKD are age, hypertension, diabetes mellitus, dyslipidemia, tobacco use, family history and male gender. In this review, we will focus on whether or not early CKD is an important risk factor for the presence, severity and progression of CVD. Specifically, we will examine both traditional and novel risk factors of both CKD and CVD and how they relate to each other. Conclusion: We will also assess if early treatment of CKD, intensive compared to standard, has an important effect on the halt of the development of CKD as well as CVD. Insights into the pathogenesis and early recognition of CKD as well as the importance of novel kidney biomarkers will be pointed out. Also, common pathogenetic mechanisms between CKD and CVD will be discussed.
Keywords: United States